Sex-Specific Associations of Diabetes With Brain Structure and Function in a Geriatric Population - Thomas, Elias G.; Rhodius-Meester, Hanneke; Exalto, Lieza; Peters, Sanne A. E.; van Bloemendaal, Liselotte; Ponds, Rudolf; Muller, Majon (Frontiers in Aging Neuroscience, 2022)
Introduction Globally, women with dementia have a higher disease burden than men with dementia. In addition, women with diabetes especially are at higher risk for cognitive impairment and dementia compared to men with diabetes. Differences in the influence of diabetes on the cerebral vasculature and brain structure may contribute to these sex-specific differences. We examined sex-specific patterns in the relationship between diabetes and brain structure, as well as diabetes and cognitive function. Methods In total, 893 patients (age 79 ± 6.6 years, 446 (50%) women) from the Amsterdam Ageing Cohort with available data on brain structures (assessed by an MRI or CT scan) and cognitive function were included. All patients underwent a thorough standardized clinical and neuropsychological assessment (including tests on memory, executive functioning, processing speed, language). Brain structure abnormalities were quantified using visual scales. Results Cross-sectional multivariable regression analyses showed that diabetes was associated with increased incidence of cerebral lacunes and brain atrophy in women (OR 2.18 (1.00 – 4.72) but not in men. Furthermore, diabetes was associated with decreased executive function, processing speed and language in women (B -0.07 (0.00 – 0.13), -0.06 (0.02 – 0.10) and -0.07 (0.01 – 0.12) resp.) but not in men. Conclusions Diabetes is related to increased risk of having lacunes, brain atrophy and impaired cognitive function in women but not in men. Further research is required to understand the time trajectory leading up to these changes and to understand the mechanisms behind them in order to improve preventive health care for both sexes.